Tensões na poesia de Eloésio Paulo - Samuel Rezende Moreira (2017)
This research approaches the poetry of Eloésio Paulo through reflections on contemporary and anachronistic concepts. This implies a theoretical framework through which both concepts are taken as temporal articulators that facilitate the dialogue and interrelation, through poetry, between the present and past. The theoretical construction allows us to find a disposition to converge, diverge, shock and tension the present and the past in the poems. In the poets work, present and past emerge to remember the history of culture in its entirety, inviting great poets, philosophers and writers of prose to think poetically the contemporary, the moment where the life is found. By creating tension between these times, Eloésios poetry simultaneously negates and remembers, but mainly reflects on the tecnopop era.